Avaliação externa de cursos de graduação: um estudo de caso em uma instituição de ensino superior - Ramos, Alessandro de Oliveira (Brasil, 2024)
The external evaluation of undergraduate programs is an essential mechanism to ensure educational quality in Brazilian Higher Education Institutions (HEIs). Regulated by the Ministry of Education (MEC) and conducted by the National Institute for Educational Studies and Research Anísio Teixeira (INEP), this practice aims to guarantee quality standards and guide course improvements, contributing to the consolidation of a more effective educational system aligned with societal demands. This study analyzes the impact of the external evaluation process on the undergraduate programs at the Federal University of Amazonas (UFAM), emphasizing the strategies and results driven by the Institutional Educational Office (PEI). The research employed a qualitative approach, collecting data through interviews and document analysis, and using action research to collaborate with participants during the investigative process. The results highlight the strategic role of the PEI in coordinating and supporting academic units, particularly in the accurate completion of electronic forms FE1 and FE2 and in preparation for on-site visits. The recent restructuring of the PEI, now linked to the Office of Undergraduate Education (PROEG), has improved the alignment of regulatory and educational activities, resulting in greater effectiveness in external evaluations. This new workflow has shown a positive impact on course assessments, with improvements in performance and strict adherence to deadlines.